Agile software development current research and future directions - Dingsøyr, Torgeir (Springer, 2010)
Agile software development has become an umbrella term for a number of changes in how software developers plan and coordinate their work, how they communicate with customers and external stakeholders, and how software development is organized in small, medium, and large companies, from the telecom and healthcare sectors to games and interactive media. Still, after a decade of research, agile software development is the source of continued debate due to its multifaceted nature and insufficient synthesis of research results. Dingsøyr, Dybå, and Moe now present a comprehensive snapshot of the knowledge gained over many years of research by those working closely with or in the industry. It shows the current state of research on agile software development through an introduction and ten invited contributions on the main research fields, each written by renowned experts. These chapters cover three main issues: foundations and background of agile development, agile methods in practice, and principal challenges and new frontiers. They show the important results in each subfield, and in addition they explain what these results mean to practitioners as well as for future research in the field. The book is aimed at reflective practitioners and researchers alike, and it also can serve as the basis for graduate courses at universities. Agile software development: an introduction and overview - Towards an understanding of the conceptual underpinnings of agile development methodologies - Agile software development methods: a comparative review - Three ‘C’s of agile practice: collaboration, co-ordination and communication - From exotic to mainstream: a 10-year odyssey from internet speed to boundary spanning with scrum - An ideal customer: a grounded theory of requirements elicitation, communication and acceptance on agile projects - Pair programming: issues and challenges - Architected agile solutions for software-reliant systems - Agile interaction design and test-driven development of user interfaces – A literature review - Organizational culture and the deployment of agile methods: the competing values model view - Future research in agile systems development: applying open innovation principles within the agile organisation.